2015
DOI: 10.2134/agronj14.0561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Tillage Depths on Sugarbeet Response and Soil Penetrability Resistance

Abstract: Tillage can alter soil properties and aff ect crop yield and quality. A 4-yr study was conducted on a Lihen sandy loam soil loam (sandy, mixed, frigid Entic Haplustoll) to evaluate the eff ect of tillage depth on sugarbeet (Beta vulgaris L.) root yield, root quality, and soil penetration resistance (PR). Tillage treatments consisted of no-tillage (NT), shallow tillage (ST), and deep tillage (DT). Soil PR was measured with a penetrometer in 2.5-cm increments to a 40-cm depth at three locations within each plot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Nonetheless, the tillage comparison was generally non-significant which agreed with findings from sugar beet studies conducted locally (Hao et al 2001;Moyer et al 2004) or in other growing regions (Koch et al 2009;Overstreet 2009;Jabro et al 2010;Stevens et al 2010). Jabro et al (2015) found that root yield and adjusted sucrose yield were not significantly affected by depth of tillage (no-till; tillage to 10 cm with a heavy-duty cultivator; or 30 cm with a ripper) in 3 of 4 yr in North Dakota.…”
Section: Conservation Management Practicessupporting
confidence: 79%
“…Nonetheless, the tillage comparison was generally non-significant which agreed with findings from sugar beet studies conducted locally (Hao et al 2001;Moyer et al 2004) or in other growing regions (Koch et al 2009;Overstreet 2009;Jabro et al 2010;Stevens et al 2010). Jabro et al (2015) found that root yield and adjusted sucrose yield were not significantly affected by depth of tillage (no-till; tillage to 10 cm with a heavy-duty cultivator; or 30 cm with a ripper) in 3 of 4 yr in North Dakota.…”
Section: Conservation Management Practicessupporting
confidence: 79%
“…Several researches, e.g. Beare et al (1994); Peixoto et al (2006); Jabro et al (2015), have shown that aggregate stability can be decreased by extensive tillage operations. Figure 3 confirms increased wet-aggregate stability, WAS, under conservation tillage practices, more specifically under RT and NT systems with mean value of WAS of 45 ± 14 %, compared to CT with WAS value of 32 ± 1 %.…”
Section: Soluble Polysaccharides and Fractions Of Organic Carbonmentioning
confidence: 99%
“…The process of fertilization should not impair the soil (heavy tractors and manure spreaders of high loading capacity excessively compact both soil and subsoil) because such harmful effects cause a reduction in crop yield for many years (Duiker 2005;Jabro et al 2015aJabro et al , 2015b. Energy assessment of the mechanical impact of agricultural machinery on soil is presented in the works of Baker (2014) and Alekseev et al (2012).…”
Section: Introductionmentioning
confidence: 99%